Kepastian Hukum Pemberian Cuti Terhadap Tenaga Kerja Outsourcing - Goklas Tambun; Miftakhul Huda (Indo Publishing, 2026)
This study aims to analyze and examine the extent to which legal certainty is realized in fulfilling leave rights for outsourced workers employed by vendor companies in Indonesia. The main focus is to examine vendor responsibilities following the enactment of Law Number 11 of 2020 concerning Job Creation and Government Regulation Number 35 of 2021. The research method used is normative juridical, focusing on the analysis of statutory regulations and principles of employment law. The results show that, normatively, legal certainty regarding leave rights has been guaranteed and is binding on vendor companies. This is based on the principle that vendor companies have full responsibility as direct employers for workers, and are therefore obliged to fulfill all normative rights, including a minimum of 12 working days of annual leave and various special leaves as stipulated in Article 79 of the Manpower Law as amended by the Job Creation Law. This certainty is reinforced by the provision that vendors are responsible for all work conditions and any disputes that arise. Despite the strong legal basis, implementation in the field faces challenges, primarily due to the complexity of the triangular employment relationship (worker-vendor-client). Coordination between workers, vendors, and service providers often creates bureaucratic hurdles in the leave application process, potentially reducing the operational certainty of these rights. Furthermore, variations in Employment Agreements drawn up by vendors can create uncertainty in implementation. The study concluded that enforcing legal certainty depends heavily on consistent supervision by the Manpower Office and the vendor company's obligation to explicitly and consistently include leave rights in employment contracts. The existence of legal sanctions for employers who violate leave obligations underscores the legal enforcement instruments available to protect the rights of outsourced workers.